Activation and Inhibition of Human Matrix Metalloproteinase-9 (MMP9) by HOCl, Myeloperoxidase and Chloramines - Yihe Wang; Christine Y. Chuang; Clare L. Hawkins; Michael J. Davies (MDPI AG, 2022)
Matrix metalloproteinase-9 (MMP9, gelatinase B) plays a key role in the degradation of extracellular-matrix (ECM) proteins in both normal physiology and multiple pathologies, including those linked with inflammation. MMP9 is excreted as an inactive proform (proMMP9) by multiple cells, and particularly neutrophils. The proenzyme undergoes subsequent processing to active forms, either enzymatically (e.g., via plasmin and stromelysin-1/MMP3), or via the oxidation of a cysteine residue in the prodomain (the "cysteine-switch"). Activated leukocytes, including neutrophils, generate O2− and H2O2 and release myeloperoxidase (MPO), which catalyzes hypochlorous acid (HOCl) formation. Here, we examine the reactivity of HOCl and a range of low-molecular-mass and protein chloramines with the pro- and activated forms of MMP9. HOCl and an enzymatic MPO/H2O2/Cl− system were able to generate active MMP9, as determined by fluorescence-activity assays and gel zymography. The inactivation of active MMP9 also occurred at high HOCl concentrations. Low (nM-low μM) concentrations of chloramines formed by the reaction of HOCl with amino acids (taurine, lysine, histidine), serum albumin, ECM proteins (laminin and fibronectin) and basement membrane extracts (but not HEPES chloramines) also activate proMMP9. This activation is diminished by the competitive HOCl-reactive species, methionine. These data indicate that HOCl-mediated oxidation and MMP-mediated ECM degradation are synergistic and interdependent. As previous studies have shown that modified ECM proteins can also stimulate the cellular expression of MMP proteins, these processes may contribute to a vicious cycle of increasing ECM degradation during disease development.